EKSPLORASI KONSEP MATEMATIKA PADA ALAT–ALAT TRADISIONAL PETANI SUKU DAYAK KAYONG UNTUK PENGUATAN PEMBELAJARAN KONTEKSTUAL DI DESA RANDAU - Seri Hani; Muchtadi; Iwit Prihatin (STKIP Subang, 2026)
This study aims to explore the mathematical concepts embedded in the traditional farming tools of the Dayak Kayong community and their relationship to strengthening contextual mathematics learning in Randau Village. The study is motivated by the importance of connecting mathematics learning with local culture so that learning becomes more meaningful and relevant for students. An ethnomathematical approach is employed to reveal mathematical concepts found in the activities and traditional tools of the Dayak Kayong farming community.The research method used is descriptive with a qualitative ethnographic approach. The research subjects include traditional leaders, traditional tool craftsmen, and farmers in Laman Kumai Hamlet, Randau Village. Data were collected through observation, interviews, and documentation, then analyzed qualitatively through data reduction, data presentation, and conclusion drawing, with triangulation used to ensure data validity.The results show that traditional tools such as canting (gantang), tanggui, and lesung contain mathematical concepts including plane figures, solid figures, measurement, number patterns, and geometry. These concepts have the potential to be integrated into contextual mathematics learning as learning resources that help improve conceptual understanding, increase learning motivation, and foster appreciation for local culture.Therefore, the traditional farming tools of the Dayak Kayong community possess ethnomathematical values that are relevant to be utilized in contextual mathematics learning.